Cardiorenal ketone metabolism in healthy humans assessed by 11C-acetoacetate PET: effect of D-β-hydroxybutyrate, a meal, and age - St-Pierre, Valérie; Richard, Gabriel; Croteau, Etienne; Fortier, Mélanie; Vandenberghe, Camille; Carpentier, André C.; Cuenoud, Bernard; Cunnane, Stephen C. (Frontiers in Physiology, 2024)
The heart and kidney have a high energy requirement but relatively little is known about their utilization of ketones as a potential energy source. We have assessed metabolism of the ketone tracer, carbon-11 acetoacetate ( 11 C-AcAc), by the left and right ventricle of the heart and by the kidney using positron emission tomography (PET) in n=10 healthy adults under four experimental conditions: a 4-hour fast (Fasted) ± a single 12 g oral dose of D-betahydroxybutyrate (D-BHB), and a single complete, liquid replacement meal (hereafter the 'Fed' condition) ± a single 12 g oral dose of D-BHB. Under these experimental conditions, the kinetics of 11 C-AcAc metabolism fitted a 2-compartment model in the heart and a 3-compartment model in the kidney. Plasma ketones were about 10-fold higher with the oral dose of D-BHB. During the four conditions, tracer kinetics were broadly similar in the myocardium and kidney cortex. 11 C-AcAc metabolism by the kidney pelvis was similar in three of the four study conditions but peaked significantly higher and later than in the cortex; the exception was that tracer uptake was significantly lower in the Fed condition without D-BHB. 11 C-AcAc uptake was significantly inversely correlated with age in the kidney cortex, and its oxidative metabolism was significantly positively correlated with age in the left ventricle. D-BHB blunted the insulin, gastric inhibitory peptide, and C-peptide response to the meal. This PET methodology and these acute metabolic perturbations would be suitable for future studies assessing cardiorenal ketone metabolism in conditions in which heart and kidney function are experimentally modified or compromised by disease. (Figure A)